2020
DOI: 10.17219/dmp/114099
|View full text |Cite
|
Sign up to set email alerts
|

Color stability of self-adhering composite resins in different solutions

Abstract: Background. The success of composite resin restorations depends to a great extent on their color stability. However, discoloration is still a problem in composite resin restorations. Objectives. The aim of the study was to evaluate the effect of different staining solutions on the color stability of composite resins. Material and methods. A total of 96 composite disks, 2 mm in height and 8 mm in diameter, were fabricated of 3 commercially available composite resins. The samples were divided into 4 groups of 8 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 20 publications
0
16
0
1
Order By: Relevance
“…Any disagreement was resolved by discussion. After full text reading 178 studies 11,13–189 were included in the review (Figure 1).…”
Section: Methodsmentioning
confidence: 99%
“…Any disagreement was resolved by discussion. After full text reading 178 studies 11,13–189 were included in the review (Figure 1).…”
Section: Methodsmentioning
confidence: 99%
“…Composite resins are esthetic restorative materials commonly used in dental clinics [10], Trevisan et al [11] state that it is currently a material of choice for direct anterior and posterior restorations due to its ease of handling, preservation of dental tissue, structural reinforcement, adhesion, low cost and especially the natural appearance of these materials. With the constant evolution of dental materials, conservative treatment has become increasingly viable, mainly because it offers advantages such as dental preservation, less working time, low cost (when compared to ceramic), and providing aesthetic results as satisfactory as [12].…”
Section: Types Of Composite Resinsmentioning
confidence: 99%
“…Today's high consumption of food and beverages full of natural and synthetic colors can result in the unsatisfactory esthetic performance of dental materials. Previous studies confirmed that esthetic brackets and adhesives are not color-stable in the long term and are susceptible to pigments commonly found in food and drinks [2][3][4][5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Intrinsic discoloration depends on the degree of polymerization of resins and adhesives, water absorption, the composition of the material, and the size and content of filler particles [ 3 , 5 , 7 ]. Moreover, UV radiation, changes in temperature and humidity, and aging of the material are also potential threats to the color stability of esthetic brackets and composite resin [ 6 , 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%